Effect of Magnetite Nano Particles on p-n-Alkyl Benzoic Acid Mesogens - S. Sreehari Sastry; S. Salma Begum; T. Vindhya Kumari; V. R. K. Murthy; Sie Tiong Ha (E-Journal of Chemistry)
The magnetite (Fe3O4) nanoparticles (0.5 wt%) of size less than 20 nm doped in p-n-alkyl benzoic acids where n varies from heptyl (7) to nonyl (9) are prepared and the presence of Fe+3 is confirmed through UV-Visible spectrophotometer. Textural and phase transition temperature studies are carried out using polarizing optical microscopy on pure and nano doped p-n-alkyl benzoic acids. These results are further confirmed by DSC at a scan rate of 5ºC/min and dielectric studies. Dielectric studies are carried out, in which the variation of dielectric constant, loss and the conductivity are analyzed with respect to temperatures and frequencies. Increment of relaxation times for nano doped heptyl and nonyl benzoic acids are observed which implies that the dielectric nature is strengthened for the nano doped mesogens. The preference of nano doped p-n-alkyl benzoic acids is discussed.